Practitioner-friendly design method to improve the seismic performance of RC frame buildings. Issue 3 (August 2021) - Arroyo, Orlando; Liel, Abbie; Gutiérrez, Sergio
Reinforced concrete (RC) frame buildings are a widely used structural system around the world. These buildings are customarily designed through standard code-based procedures, which are well-suited to the workflow of design offices. However, these procedures typically do not aim for or achieve seismic performance higher than code minimum objectives. This article proposes a practical design method that improves the seismic performance of bare RC frame buildings, using only information available from elastic structural analysis conducted in standard code-based design. Four buildings were designed using the proposed method and the prescriptive approach of design codes, and their seismic performance is evaluated using three-dimensional nonlinear (fiber) models. The findings show that the seismic performance is improved with the proposed method, with reductions in the collapse fragility, higher deformation capacity, and greater overstrength. Furthermore, an economic analysis for a six-story building shows that these improvements come with only a 2% increase in the material bill, suggesting that the proposed method is compatible with current project budgets as well as design workflow. The authors also provide mathematical justification of the method.